2019
DOI: 10.1111/ceo.13515
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for visual acuity in patients with Leber's hereditary optic neuropathy after rAAV2‐ND4 gene therapy

Abstract: Importance Factors affecting visual acuity prognosis after gene therapy in Leber's hereditary optic neuropathy (LHON) patients with mutation at site 11 778 are unknown. Background To analyse correlations between visual acuity prognosis and baseline characteristics of LHON after rAAV2‐ND4 gene therapy. Design Retrospective study. Participants Fifty‐three LHON patients with a mutation at site 11 778. Methods Single‐eye intravitreal injection of rAAV2‐ND4. Main Outcome Measures Sex, onset age, duration of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
(49 reference statements)
0
21
0
1
Order By: Relevance
“…At three months after injection, they found significant differences in baseline visual acuity and visual field index, but not age at onset, between the groups with and without a three-line improvement in logMAR. Logistic regression analysis confirmed that only baseline visual acuity and visual field index were significant in the visual acuity improvement [31], indicating no role for age at onset.…”
Section: Prognostic Factorsmentioning
confidence: 86%
“…At three months after injection, they found significant differences in baseline visual acuity and visual field index, but not age at onset, between the groups with and without a three-line improvement in logMAR. Logistic regression analysis confirmed that only baseline visual acuity and visual field index were significant in the visual acuity improvement [31], indicating no role for age at onset.…”
Section: Prognostic Factorsmentioning
confidence: 86%
“…The first included 142 LHON patients with the m.11778G>A/ MTND4 mutation, 69 more than 24 months after onset and 73 less than 24 months prior to onset; BCVA and VF were the primary outcomes and the final results are expected soon. Retrospective studies on the injected patients showed that greater VF index, smaller VF mean deviation and higher BCVA at baseline predicted a better VA prognosis [ 181 ], and that baseline BCVA and time between onset and treatment are predictors of rapid visual improvement, in both injected and not-injected eyes [ 182 ]. To explain the rapid recovery, within days after treatment, it has been suggested that in some patients a portion of RGCs survive in a “dormant” state that can be activated by gene therapy [ 179 ].…”
Section: Therapeutic Options In Mitochondrial Optic Neuropathiesmentioning
confidence: 99%
“…The sponsor of this study, Huazhong University of Science and Technology, is conducting a larger phase II/III study with 142 subjects to confirm the promising safety, efficacy, and durability of rAAV2-ND4 gene therapy (NCT03153293). Initial 3-month results of this larger scale study looked at the baseline functional characteristics that correlated with visual recovery (82). Better baseline visual field index (VFI) and BCVA were found to be strong predictors of functional improvement (82).…”
Section: Leber Hereditary Optic Neuropathy (Lhon)mentioning
confidence: 99%
“…Initial 3-month results of this larger scale study looked at the baseline functional characteristics that correlated with visual recovery (82). Better baseline visual field index (VFI) and BCVA were found to be strong predictors of functional improvement (82).…”
Section: Leber Hereditary Optic Neuropathy (Lhon)mentioning
confidence: 99%